Biosynthesis of phenylpyruvic acid from l‐phenylalanine using chromosomally engineered Escherichia coli. (12th October 2021) - Xiong, Tianzhen; Bai, Yajun; Fan, Tai‐Ping; Zheng, Xiaohui; Cai, Yujie
Abstract: The efficiency of whole‐cell biotransformation is often affected by the genetic instability of plasmid‐based expression systems, which require selective pressure to maintain the stability of the plasmids. To circumvent this shortcoming, we constructed a chromosome engineering strain for the synthesis of phenylpyruvic acid (PPA) from l ‐phenylalanine. First, l ‐amino acid deaminase ( pmLAAD ) from Proteus myxofaciens was incorporated into Escherichia coli BL21 (DE3) chromosome and the copy numbers of pmLAAD were increased by chemically induced chromosomal evolution (CIChE). Fifty‐nine copies of pmLAAD were obtained in E. coli BL8. The PPA titer of E. coli BL8 reached 2.22 g/L at 6 h. Furthermore, the deletion of lacI improved PPA production. In the absence of isopropyl‐β‐d ‐thiogalactopyranoside, the resulting strain, E. coli BL8△ recA △ lacI, produced 2.65 g/L PPA at 6 h and yielded a 19.37% increase in PPA production compared to E. coli BL8△ recA . Finally, the engineered E. coli BL8△ recA △ lacI strain achieved 19.14 g/L PPA at 24 h in a 5‐L bioreactor. Abstract : The engineering strain was constructed by chemically induced chromosomal evolution and converted L‐phenylalanine into phenylpyruvic acid.